Oceanographic and biological prospecting in the south of Peru during "El Niño 1997-98" - Quiroz, Marco (1999)
The oceanographíc and biological condítions were studied in the south zone of Peru in 36 stations distributed in perpendicular profiles respect to the coast until 80 MN, from January 13th to 16th of 1998, during the phase of major intensity of "El Niño 1997-98".The results showed a generalized presence of subtropical superficíal water, with a poverty of phytoplankton densíty and diversity; and very low densities of pelagic resources, as a consequence of deepening or southward migration of the shoals.